2012
DOI: 10.1002/jqs.2554
|View full text |Cite
|
Sign up to set email alerts
|

Central England temperature since AD 1850: the potential of stable carbon isotopes in British oak trees to reconstruct past summer temperatures

Abstract: In regions with seasonal temperate climatic regimes, tree growth is rarely controlled by any single environmental factor. As a consequence, the development of robust palaeoclimate reconstructions has proved challenging. Tree-ring stable carbon isotope ratios (d 13 C), however, are controlled primarily by photosynthetic rate, not by net growth. Therefore, at sites where climatic controls on tree-ring growth are not strongly expressed, a robust (isotopic) palaeoclimate signal may still potentially be preserved. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 89 publications
(110 reference statements)
1
33
0
Order By: Relevance
“…Nevertheless, the pin-correction has been applied to pooled chronologies (e.g. Young et al, 2012). Szymczak et al (2012) developed carbon isotope chronologies of 5 individual trees from one site as well as a pooled chronology consisting of the same 5 trees for a common time period (1961.…”
Section: Carbon Isotopes In Tree-ring Cellulose As Climate Proxymentioning
confidence: 99%
“…Nevertheless, the pin-correction has been applied to pooled chronologies (e.g. Young et al, 2012). Szymczak et al (2012) developed carbon isotope chronologies of 5 individual trees from one site as well as a pooled chronology consisting of the same 5 trees for a common time period (1961.…”
Section: Carbon Isotopes In Tree-ring Cellulose As Climate Proxymentioning
confidence: 99%
“…Loader et al, 2008;Saurer et al, 2008;Young et al, 2012). They can help extend climate reconstructions into regions which are not yet well covered , and also provide information about precipitation amount (Rinne et al, 2013;Young et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Measurements of the stable carbon, oxygen and hydrogen isotope ratio exhibit a statistically significant relationship with environmental variables such as temperature, precipitation, drought, sunshine, cloud cover (Gori et al, 2013;Hilasvuori & Berninger, 2010;Loader et al, 2008;McCarroll et al, 2003;Treydte et al, 2007;Young et al, 2012). The mechanisms responsible for the isotope fractionation in tree rings are fairly well-known (Farquhar et al, 1982;Gessler et al, 2014;McCarroll & Loader, 2004;Waterhouse et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Although strong correlations between isotopic and instrumental data from temperate areas such as Britain (Loader et al, 2003;Loader et al, 2008;Robertson et al, 1997b), Northern France (Etien et al, 2009), Southern Finland (Hilasvuori & Berninger, 2010 and Swiss Central Plateau (Saurer et al, 2008) were evaluated, and only one publication concerning the climate reconstruction of the site neither strongly limited by temperature nor precipitation (temperature in Central England) (Young et al, 2012) was found.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation